Trophic Structure and Vulnerability of Fish Species Exploited by Bottom Gillnet in the Coastal Waters of Lambur Luar Village, Jambi, Indonesia - Rizky Janatul Magwa; Ade Khairunisa; Mairizal; Ester Restiana Endang Gelis; Yoppie Wulanda; Lauura Hermala Yunita; Muhammad Hafidz Ibnu Khaldun; Yusyam Leni; Febrina Rolin (Journal of Fish Health, 2026)
Small-scale fisheries in coastal areas utilize various fishing gears, including bottom gillnet, which can catch fish species with different trophic levels. Fishing activities may influence the trophic structure of fish communities and the vulnerability of species to exploitation. This study aimed to analyze the trophic structure, vulnerability level, conservation status based on the IUCN Red List, and Mean Trophic Level (MTL) of fish species caught using bottom gillnet in the coastal waters of Lambur Luar Village, Tanjung Jabung Timur Regency. The study used a survey method with data collected through direct observation of fishermen's catches. Data analysis included catch species composition, trophic level values ​​obtained from the FishBase database, vulnerability analysis of each species, identification of IUCN conservation status, and calculation of Mean Trophic Level (MTL) based on the proportion of catch composition. The results showed that the catches consisted of 20 species, with trophic groups dominated by mesopredators (50%) and top predators (25%), while omnivores and herbivores were found in smaller proportions. Vulnerability analysis indicated that most species were categorized as having low to moderate vulnerability, although several species showed high vulnerability to fishing pressure. Based on the IUCN Red List, most species were classified as Least Concern (LC). The calculated Mean Trophic Level (MTL) was 3.2, indicating that the catches were dominated by mid-level carnivorous fish species.